A MOBILIDADE URBANA EM CAMAÇARI-BA: A CRISE NO SISTEMA DE TRANSPORTE URBANO E A ATUAÇÃO DOS “LIGEIRINHOS” (Publicatio UEPG: Ciências Sociais Aplicadas, 2024)
This article discusses mechanisms that favored the emergence and intensification of unregulated alternative transport, popularly known as "ligeirinho" in the city of Camaçari/BA, with emphasis on the deficiency of local urban transport associated with unemployment. In this scenario, the performance dynamics of the mode of transport in question and the struggle of the different social actors in favor of its regulation are exposed together with the calamity declaration of the city's transport system, seeking to highlight the crisis in local urban mobility and the popularity of the alternative service. Then, the legislation that governs mobility and the possibility of regulating the category of alternative transport is discussed. Then, an analysis will be made of the main impasses that have prevented the elaboration of a specific law that regulates the “ligeirinho”, in addition to demonstrating how the local public power is positioned in relation to the search for a solution to the problem.